The underpricing of initial public offerings and the partial adjustment phenomenon - Hanley, Kathleen Weiss (Journal of Financial Economics, 1993)
This paper documents that the relation of the final offer price to the range of anticipated offer prices disclosed in the preliminary prospectus is a good predictor of initial returns. Issues that have final offer prices which exceed the limits of the offer range have greater underpricing than all other initial public offerings, and are also more likely to increase the number of shares issued. These results are consistent with the pricing and allocation schedule proposed by Benveniste and Spindt (1989), in which shares in an offering are rationed and prices only partially adjust to new information.